The Golden Ratio in Schwarzschild–Kottler Black Holes - Cruz-Marin, N (Springer New York LLC, 2017)
In this paper we show that the golden ratio is present in the Schwarzschild–Kottler metric. For null geodesics with maximal radial acceleration, the turning points of the orbits are in the golden ratio Φ=(5-1)/2. This is a general result which is independent of the value and sign of the cosmological constant Λ. © 2017, The Author(s).